MANAJEMEN KOMPLAIN PADA PENGKAJIAN DAN PENGEMBANGAN TEKNOLOGI INFORMASI (PPTI) UNIVERSITAS BRAWIJAYA - Risda Amalia (REFORMASI, 2015)
Public service is a complex administration practice. Hence, it might cause maladministration resulting in a complaint as a kind of response that should be accepted as a feedback of service. That’s why, some people said that complaint is an expression of customer’s loyalty that should be respected in anywhere, especially in a University named Universitas Brawijaya, Malang as a part of management in public administration. Inside Universitas Brawijaya, there is a service unit named PPTI (Unit Pengkajian dan Pengembangan Terknologi Informasi/Unit of Information Technology Study and Development).